2018
DOI: 10.1111/tra.12624
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the anterograde trafficking of GPCRs: Regulation of AT1R transport by interacting proteins and motifs

Abstract: Anterograde cell surface transport of nascent G protein‐coupled receptors (GPCRs) en route from the endoplasmic reticulum (ER) through the Golgi apparatus represents a crucial checkpoint to control the amount of the receptors at the functional destination and the strength of receptor activation‐elicited cellular responses. However, as compared with extensively studied internalization and recycling processes, the molecular mechanisms of cell surface trafficking of GPCRs are relatively less defined. Here, we wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 172 publications
(259 reference statements)
0
19
0
Order By: Relevance
“…GPCRs are co-translationally inserted into the membrane of the ER [ 18 , 19 ]. They are then trafficked in vesicles along the secretory pathway of the cell, passing the membranes of the ERGIC and the Golgi apparatus [ 20 ], before reaching the plasma membrane. Towards the end of their lifetime, GPCRs are internalised from the cell surface into the membranes of endosomes [ 21 ].…”
Section: Cellular Trafficking Of Membrane Lipids and Gpcrsmentioning
confidence: 99%
“…GPCRs are co-translationally inserted into the membrane of the ER [ 18 , 19 ]. They are then trafficked in vesicles along the secretory pathway of the cell, passing the membranes of the ERGIC and the Golgi apparatus [ 20 ], before reaching the plasma membrane. Towards the end of their lifetime, GPCRs are internalised from the cell surface into the membranes of endosomes [ 21 ].…”
Section: Cellular Trafficking Of Membrane Lipids and Gpcrsmentioning
confidence: 99%
“…The synthesis and transfer of newly formed proteins via secretory pathways from the ER to the PM is a complex process involving different mechanisms and many additional proteins and motifs that are important in protein interaction and enable their proper formation, quality control, selective retention, and transport [ 46 ]. Mechanisms that regulate the secretory transport of GPCRs or their transfer to the cell surface are poorly elucidated [ 47 , 48 ]. It is known that the interconnection of the same or different GPCRs, homo- and heterodimerization, is essential in the transport of GPCRs in families A and C, but not for representatives of family B on the PM [ 49 ].…”
Section: The Er Retention Motifs In Gpcrs and Both Dmentioning
confidence: 99%
“…For D 1 -R it was shown that the ER-membrane-associated protein DRiP78 binds to a FXXXFXXXF motif in the C-terminus of D 1 -R and other GPCRs. Overexpression or down-modulation of this putative two-TM domain protein leads to ER retention of D 1 -Rs, reduced ligand binding, and impaired kinetics of receptor glycosylation [ 48 ]. This mechanism acts as a chaperone and may control PM receptor targeting without traveling to the cell surface.…”
Section: -R Interaction Proteins (Drips)mentioning
confidence: 99%
“…In particular, Daniel et al show that PIK3C2A regulates the surface delivery of the delta opioid receptor (δR) and δR-mediated cyclic adenosine monophosphate (cAMP) inhibition. Further, they display how this mechanism is not only present in neuronal cells, but also in epithelial cells [60,61].…”
Section: Pik3c2amentioning
confidence: 99%